Metagenomics-based systematic analysis reveals that gut microbiota Gd-IgA1-associated enzymes may play a key role in IgA nephropathy - Liang, Xiaolin; Zhang, Simeng; Zhang, Difei; Hu, Liang; Zhang, La; Peng, Yu; Xu, Yuan; Hou, Haijing; Zou, Chuan; Liu, Xusheng; Chen, Yang; Lu, Fuhua (Frontiers in Molecular Biosciences, 2022)
Background: IgA nephropathy (IgAN) is the most common type of glomerulonephritis in Asia. Its pathogenesis involves higher expression of galactose-deficient IgA1 (Gd-IgA1) and dysregulated intestinal mucosal immunity. The objective of this study was to explore whether specific gut microbiota and associated enzymes affect Gd-IgA1 in IgAN. Methods: This study carried out shotgun metagenomic sequencing with Illumina on fecal samples collected from 20 IgAN patients (IgAN group) and 20 healthy controls (HCs group) who were recruited from January 2016 to December 2018 at the Second Clinical College of Guangzhou University of Chinese Medicine. Differences analysis in gut microbiota was performed to determine the overall microbiota composition, the representative enterotypes, and the microbiota abundance. Correlations between gut microbiota and clinical indicators were assessed by Spearman’s analysis. Moreover, the functional prediction of microbial communities and the quantitative calculation of enzymes encoded by microbiome were performed using the MetaCyc pathway and the bioBakery 3 platform, respectively. Results: Bacteroides plebeius and Bacteroides vulgatus levels were higher, while Prevotella copri and Alistipes putredinis levels were lower in the IgAN group compared to HCs group. Enterotype I characterized by Bacteroides was closely related to the IgAN patients. Moreover, Bacteroides fragilis, Flavonifractor plautii and Ruminococcus gnavus were characteristic bacteria enriched in IgAN patients. Spearman’s correlation analysis found that Eggerthella lenta and Ruminococcus bromii were positively correlated with urine protein-creatinine ratio, while Ruminococcus gnavus showed a direct association with red blood cells in urine, and Bacteroides vulgatus and Ruminococcus gnavus were positively correlated with eGFR. These results indicated that intestinal dysbacteriosis occurred in IgAN patients and was associated with clinical and biochemical features. In addition, MetaCyc pathway analysis predicted microbiota-related metabolic pathways, including the biosynthesis of amino acids and glycans, were associated with the IgAN group. Microbial enzymes analysis highlighted that Gd-IgA1-associated α-galactosidase and α-N-acetyl-galactosaminidase secreted by Flavonifractor plautii were enriched in IgAN patients. Conclusion: These findings suggested that α-galactosidase and α-N-acetyl-galactosaminidase secreted by Flavonifractor plautii might be related to the production of Gd-IgA1, indicating that enzymes originated from abnormal intestinal microbiota may contribute to the production of Gd-IgA1 and play an important role in the pathogenesis of IgAN.